Role of Calcium Channels in Heavy Metal Toxicity. (30th January 2013) - Marchetti, Carla
Abstract : The role of voltage-dependent Ca channels (VDCC) in the membrane permeation of two toxic metals, lead (Pb) and cadmium (Cd), was studied in mammalian cells. Both metals interact with Ca-binding sites, but, while Cd influx appears to occur mainly through the same pathways as Ca, Pb is also rapidly taken up by different passive transport systems. Furthermore, I compared the effect of Cd in two Chinese hamster ovary (CHO) cell lines, a wild-type and a modified cell line, which were permanently transfected with an L-type VDCC. When cultures were subjected to a brief (30–60 min) exposure to 50–100  μ M Cd, apoptotic features, metal accumulation, and death were comparable in both cell lines although, in transfected cells, the effect of Cd treatment was partially prevented by nimodipine (VDCC antagonist) and enhanced by BayK8644 (VDCC agonist). Thus, expression of L-type Ca channels is not sufficient to modify Cd accumulation and sensitivity to a toxicological significant extent and while both Cd and Pb can take advantage of VDCC to permeate the membrane, these transport proteins are not the only, and frequently not the most important, pathways of permeation.